Respuesta :

Answer:

see explanation

Step-by-step explanation:

Calculate the slope m using the slope formula

m = (y₂ - y₁ ) / (x₂ - x₁ )

with (x₁, y₁ ) = 2,4 ) and (x₂, y₂ ) = (5, 1)

m = [tex]\frac{1-4}{5-2}[/tex]  = [tex]\frac{-3}{3}[/tex] = - 1 ← negative slope

Repeat

with (x₁, y₁ ) = - 7,8) and (x₂, y₂ ) = (- 7, 0)

m = [tex]\frac{0-8}{-7+7}[/tex] = [tex]\frac{-8}{0}[/tex]

Division by zero is undefined, thus slope is undefined.

Repeat with

(x₁, y₁ ) = (6, - 3) and (x₂, y₂ ) = (- 4, - 3)

m = [tex]\frac{-3+3}{-4-6}[/tex] = [tex]\frac{0}{-10}[/tex] = 0 ← zero slope

Repeat with

(x₁, y₁ ) = (3, 5) and (x₂, y₂ ) = (- 1, 2)

m = [tex]\frac{2-5}{-1-3}[/tex] = [tex]\frac{-3}{-4}[/tex] = [tex]\frac{3}{4}[/tex] ← positive slope

ACCESS MORE
EDU ACCESS
Universidad de Mexico